Cost-cutting: A strategy for greater wealth and employment? Results of quantitative scenarios for Germany to the year 2010 - Claudius Schmidt-Faber; Martin Gornig; Bernd Görzig; Erika Schulz (Deutsches Institut für Wirtschaftsforschung (DIW), 1999)
[Introduction] Germany currently finds itself in a difficult economic situation, one characterised not only by a long period of weak economic growth, but also by developments that, if the necessary adjustment processes are not accomplished, pose a threat to Germany's medium-term growth prospects. In the international context the central challenges result from the following trends: * Changes in the framework of conditions for international trade (WTO agreements), which offer new opportunities for the export sector, but can also be expected to intensify competition and thus the pressure for adjustment; * the transition in eastern Europe, the opening up of China and developments in Latin America, all of which, on the one hand, offer new sales markets for German companies, but on the other create new competitive relations and alternative locations for production and investment; * the trend towards globalisation, which is gradually dissolving traditional ties to production locations.
Keywords: 330; Produktionskosten; Angebotsorientierte Wirtschaftspolitik; Lohnpolitik; Steuerreform; Sozialreform; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Deutschland